COMPARISON OF SURVIVAL PERIODS AND RESPONSE IN THREE MODES OF TREATMENT FOR Ca ESOPHAGUS AT CENAR QUETTA - ullah, Rooh; Khurshed, MA; Haider, SW; Kamran, S; Farah, Kh.; Burdy, GM (Journal of Ayub Medical College Abbottabad, 2004)
Background: Esophageal cancer is a fatal disease, with mortality matching the incidence. Balochistan province and Afghanistan happen to fall in the "Esophageal Cancer Belt". This study was designed to compare survival periods and response in three different modes of treatment for cancer of esophagus at CENAR Quetta i.e Radiotherapy plus Surgery, Radiotherapy plus Surgery plus single agent chemotherapy and Radiotherapy plus Surgery plus combined chemotherapy. Methods: During 1997, 59 patients with histopathological evidence of Ca esophagus were referred to CENAR from primary health care centers in Balochistan and Afghanistan. These 59 patients were divided into three groups. Group:I (n=22) treated by local irradiation plus surgery. Group:II (n=20) treated by local irradiation plus surgery plus Single agent chemotherapy i.e 5 florouracil. Group:III (n=17) treated by local irradiation plus surgery plus combination chemotherapy i.e Cis-Platinum and 5-florouracil. All patients were evaluated by endoscopic examination at 2 month intervals. Results: This study of 59 patients (mean age 55±13 years and male to female ratio of 1:3), shows that 2 year survival is 29% and median survival period is 9 month for all the patients. For group 1, median survival period = 5 month, 2 year survival =18% and complete response =17%. For group II, Median survival period = 9 months, 2 year survival =30% and complete response =20%. For group III, Median survival period = 11 month, 2 year survival = 41% and complete response = 22%.Conclusion: This study shows that overall survival is poor in cancer of esophagus and combined chemotherapy along with surgery and radiotherapy gives better results as compared to other two groups. Also single agent chemotherapy plus surgery plus radiotherapy give better results than radiotherapy plus surgery. Keywords: Ca Esophagus, Chemotherapy, Radiation therapy